Usage of Potential Micro-organisms for Degradation of Plastics - Rafia Riaz; Darakhshanda Iram; Rana K Iqbal (Open Journal of Environmental Biology - Peertechz Publications, 2019)
Plastics are high molecular weight organic source materials. It is necessary to devise systems to decompose plastic polymers because their disruptive effects are threatening the ecosystem. Biotic and abiotic strategies are being employed to convert plastics into monomers. The objective of both techniques is to reduce polymers to monomers. Microbes act on monomers for their degradation by releasing enzymes on polymers. The rate of microbial degradation is affected by both the environmental conditions as well as by polymer characteristics. Different methods are used to check the rate of biological degradation However, some plastics oppose microbial action. The environment condition and polymer characteristics affect the rate of degradation. Different approaches are used to check the rate of biological degradation. The need of the time is to generate bio based plastics material which can be degraded efficiently. These polymers can be recycled by degradation to monomers and then convert back to petrochemical products. This will contribute to fulfill the increasing demand of organic fuels and may serve as next generation fuel. There is no effective technique that can degrade plastics with efficacy, so scientists are struggling to develop techniques which not only degrade these polymers but also results into beneficial products. This review is an attempt to organize some of the most common strategies for degradation of various types of polymers along with a list of potential microbes capable of feeding on them.